Manajemen Keuangan Rumah Tangga Pada Kelompok Pemberdayaan Dan Kesejahteraan Keluarga (PKK) Batang Pekalongan - Ulfa Kurniasih, Ulfa Kurniasih (JCSE: Journal of Community Service and Empowerment, 2023)
This program is focused on the women of the Empowerment and Family Welfare Group (PKK) Perum Saputra Raya 1 Cepokokuning Batang, Pekalongan to improve their ability to carry out financial management. Most of the service partners come from the middle class but still have difficulty managing household finances. This program is carried out by implementing 3 stages, namely preparation, implementation, and evaluation. The preparatory stage consisted of outreach and FGD to PKK managers at Perum Saputra Raya 1 Cepokokuning Batang, Pekalongan. The implementation phase is divided into 2 parts, namely material regarding household financial management and the practice of implementing household financial management. In the material section, information is provided regarding the household financial planning process based on the category of budget allocation. These categories consist of basic needs, secondary needs, social needs, and emergency funds. At the evaluation stage there was an increase in participants' understanding of household financial management. This can be seen from the participants' ability to determine the priority scale of household needs based on predetermined financial allocations.